Internalisasi Karakter Religius Islam Anak Melalui Suplementasi Sastra Digital 'Kusuma' (Aku Suka Ke Masjid) - Nur Asiyah; Lunfianka Sanjaya; Yustin Sartika; Hidayatul Nurjanah (Transformatif : Jurnal Pengabdian Masyarakat, 2021)
This community service activity was motivated by the importance of religious character education as the basic foundation of character education. The aim of this activity was to implement method and media which suitable for children’s characteristic ‘to play’ as an attempt to internalize the value of religious character. This community service activity was held in TPQ Baiturahman Boyolali by using combination of method : observation,discussion and mentoring. The result of this community service activity were 1) game can be used as a media to introduce the value of religious character to children, 2) Emotional strengthening, motivation and habituation are needed to accompany children being someone who is beneficial for others.